A facile and fast method for quantitating lignin in lignocellulosic biomass using acidic lithium bromide trihydrate (ALBTH). Issue 19 (18th July 2016) - Li, Ning; Pan, Xuejun; Alexander, Jane
Abstract : A facile (one-step) and fast (30 min) method (ALBTH) was developed to quantitate lignin in lignocellulosic biomass; the method gave comparable results with the Klason method. Abstract : Lignin quantitation of lignocellulosic biomass is an essential and routine assay in the areas of plant chemistry, forage, biomass conversion, and pulp & paper. The two-step sulfuric acid method (or the Klason method) is the most widely used protocol for lignin quantitation, but the method is a time-consuming and labor-intensive procedure. In this study, a facile and quick method was developed to quantitate lignin in lignocellulosic biomass. The new method used acidic lithium bromide trihydrate (ALBTH, LiBr·3H2 O) as a reaction medium, which was able to quickly and completely dissolve and hydrolyze cellulose and hemicelluloses in the biomass under mild conditions and leave lignin as an insoluble residue for gravimetric quantitation. The soluble lignin generated in the ALBTH assay was determined by UV spectrophotometry. The recommended conditions for the ALBTH method were 60 wt% LiBr solution containing 40 mM HCl, 110 °C, and 30 min. The ALBTH method was applied to different species of biomass including softwood (Douglas fir), hardwood (aspen, poplar, and eucalyptus), and herbage (corn stover and switchgrass). The results indicated that the ALBTH method gave a comparable lignin (both insoluble and soluble lignin) quantity with the Klason method for the biomass investigated. The ALBTH method is a one-step procedure and much faster for lignin quantitation (∼30 min) than the Klason method (>3 h). In addition, the ALBTH assay was conducted in glass vials under atmospheric pressure, and no autoclave was required. The ALBTH method also avoided the potential hazard of concentrated sulfuric acid.